(untitled) (Heritage, 2022)
The paper deals with the analysis of textbooks for the subject Music Culture for the younger grades of primary school with the aim to determine the extent to which they contribute to strengthening the national identity of students. In order to make the results relevant, the textbooks of five publishers, designed for the first, second, third and fourth grade, were analyzed. A quantitative analysis of the contents was carried out and contents related to encouraging the development of national identity were identified. Also, it was analyzed the didactic-methodical apparatus which is related to national identity, that accompanies the basic text. Pictorial contents and general information that interprets songs or compositions for listening are highlighted. Quantitative analysis of contents shows that no publisher offered students a third of these contents. The anthem of the Republic of Serbia is not foreseen in certain textbooks, while in the textbooks of other publishers the authors did not foresee any patriotic song. The second part of the analysis shows that mentioned contents, which are given in a modest volume, are not accompanied by pictorial contents or information that further explains the songs or compositions for listening. On average, pictorial contents follow only a third, and general information only a quarter of contents related to national identity. The results of the research indicate that there are not enough contents that contribute to the strengthening of national identity in the textbooks for Music Culture, that they are very little accompanied by pictorial contents, while there is almost no general information.